Living and Dead Microorganisms in Mediating Soil Carbon Stocks Under Long-Term Fertilization in a Rice-Wheat Rotation - Chen, Jie; Song, Dali; Luan, Haoan; Liu, Donghai; Wang, Xiubin; Sun, Jingwen; Zhou, Wei; Liang, Guoqing (Frontiers in Microbiology, 2022)
Although soil microorganism is an active area of research, we are still in the early stages of understanding how living microorganisms influence the accumulations of soil microbial residues under different agricultural practices. Based on a 39-year fertilization experiment, we characterized the soil microbiota and correlated their compositions to soil microbial residues which are indicated by amino sugars under a rice-wheat rotation. In the present study, fertilization regimes and crop season all exerted significant impacts on the compositions of soil microbial communities and their residues, while no significant difference in the microbial residues was found between soil depth (0–10 cm vs. 10–20 cm). Compared within fertilization regimes, long-term fertilization, especially the application of organic manure, stimulated the accumulations of carbon (C) and nitrogen in soils and microbial residues. Upland soils in wheat season accumulated more microbial residues, particularly in fungal residues, than paddy soils in rice season. Our results suggested that long-term application of organic manure favored the growth of soil microbial communities, then increased the contents of microbial residues, particularly in fungal residues, leading to an enlargement of soil C pools. The keystone taxa Pseudaleuria identified by network analysis showed a significantly positive potential in soil C sequestration by increasing the accumulations of fungal residues. Thus, this study revealed the strong and close connections between microbial communities and their residues, and provided evidence about the critical role of keystone taxa in regulating C sequestration.